Efficiency of Indian General Insurance Companies: Convex Nonparametric Least Squares Approach - Sinha, Ram Pratap; Cvetkoska, Violeta; Peovski, Filip (Croatian Operational Research Society, 2022)
In the current millennium, the Indian general insurance market has witnessed major structural changes because of the establishment of a market regulator and the initiation of entry deregulation. The present study evaluates the efficiency performance of fifteen Indian general insurance companies for the period 2011/12 - 2016/17 using a robust nonparametric approach. The study also seeks to explain efficiency by considering the influence of environmental variables on the efficiency scores. The results indicate that efficiency is positively related to ownership, insurer age, market share, and return on equity but negatively related to size.
Keywords: convex nonparametric regression, efficiency, general insurance, quantile regression